Fluoropolymers and Their Nanohybrids As Energy Materials: Application to Fuel Cells and Energy Harvesting - Prakash O.; Tiwari S.; Maiti P. (My University, 2025)
The current review article provides deep insight into the fluoropolymers and their applications in energy technology, especially in the field of energy harvesting and the development of fuel cell electrolyte polymeric membranes. Fluoropolymers have gained wide attention in the field of energy applications due to their versatile properties. The incorporation of nanofillers within the fluoropolymer to develop the nanohybrid results in an enhancement in the properties, like thermal, mechanical, gas permeation, different fuel cross-over phenomena through the membrane, hydrophilic/hydrophobic nature, ion transport, and piezo-electric properties for fabricating energy devices. The properties of nanohybrid materials/membranes are influenced by several factors, such as type of filler, their size, amount of filler, level of dispersion, surface acidity, shape, and formation of networking within the polymer matrix. Fluoropolymer-based nanohybrids have replaced several commercial materials due to their chemical inertness, better efficacy, and durability. The addition of certain electroactive fillers in the polymer matrix enhances the polar phase, which enhances the applicability of the hybrid for fuel cell and energy-harvesting applications. Poly(vinylidene fluoride) is one of the remarkable fluoropolymers in the field of energy applications such as fuel cell and piezoelectric energy harvesting. In the present review, a detailed discussion of the different kinds of nanofillers and their role in energy harvesting and fuel cell electrolyte membranes is projected. © 2022 The Authors. Published by American Chemical Society.